Pengaruh Lingkungan Kerja Dan Motivasi Terhadap Kinerja Karyawan Pada Sekolah Tinggi Pariwisata Bogor - Ananda Puteri Az Zahra; Muhamad Azis Firdaus; Agung Wibowo (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research aims to determine the influence of the work environment and motivation on employee performance at the Bogor Tourism College. This research was conducted using quantitative methods. The data collection technique was carried out by distributing questionnaires to 77 employees of the Bogor Tourism College, which were then processed using the Smartpls 4.0 application using the SEM (Stuctural Equation Modeling) analysis method. The results obtained from the influence of the Work Environment on Employee Performance with an original sample value of 0.328, T Statistics 1.982 > 1.96 and P-values 0.024 < 0.05 means that there is a positive and significant influence between the Work Environment and Employee Performance. The results obtained from Motivation on Employee Performance with an original sample value of 0.590, T Statistics 3.628 > 1.96 and P-values 0.000 < 0.05 means that there is a positive and significant influence between Motivation on Employee Performance. The results obtained from the influence of the Work Environment on Motivation with an original sample value of 0.920, T Statistics 64,976 > 1.96 and P-values 0.000 < 0.05, meaning that there is a positive and significant influence between the Work Environment and Motivation. The results obtained from the influence of the Work Environment on Employee Performance through Motivation with an original sample value of 0.543, T Statistics 3.838 > 1.96 and P-values 0.000 < 0.05 means that there is a positive and significant influence between the Work Environment on Employee Performance through Motivation.